The New Normal In Educational Administration After The Covid-19 Crisis - Duangchurn, Patcharaporn (Arts of Management Journal, 2020)
The purpose of this study was to provide management ideas for school administrators after the COVID-19 crisis under a new lifestyle that is different from the past. Due to the fact that there are some things affecting until we have to change to a new normal, we used to leave home to work and study, but now we have to stay at home. If there is a need to go out of the house for shopping or even to see a doctor. We must wear masks to prevent disease, keep distance for the person, often wash hands for 230 seconds, wipe hands with alcohol, etc. The concept of educational management in accordance with the new normal is the preparation of online teaching for equipment and technology, the curriculum design taking into account the differences of each student, the schools and teachers management for a successful learning through discussions and participatory planning of the parties involved in all sectors; policy makers, school administrators, teacher, educational staff, entrepreneurs in the business sector and civil society, parents, including physical and mental preparation of teacher and students.